Pengaruh Faktor Sosial Ekonomi Dan Kompetensi Manajerial Peternak Sapi Perah Terhadap Pendapatan (Suatu Kasus Pada Peternak Sapi Perah di KPSBU Lembang di Kecamatan Lembang, Kabupaten Bandung Barat) - Euis Dasipah; Karyana KS; Dety Sukmawati; Ida Danah (Paspalum: Jurnal Ilmiah Pertanian, 2020)
The research has aim at to know relationship between  the socio economic factors and managerial competence and and it’s infuence to the breeder’s income.    The method was  used by survey technique toward the breeders.  The Sampling technique was used by simple random sampling method by using slovin formula, carried out 70 units. The data was analyze by the  path analyze to  verify  the hypothesis. The result of the research that was the relationship strongly between  the influence of socio economic factors and managerial competence shown by the coeficient of corellation r = 0,77.  The economic factors has  the indicators : age, formal education, knowledge, experience, dependency ratio,  motivation of business and scale of business has gained 78,53% citeria good.  Managerial competence of breeder has  indicators: data recording,  milking technique , livestock health, feed, mating,cowshed, man power and marketing  obtained   78,94 %,  criteria good.  The  socio economic factors and managerial competence of breeder give  a positive influence to the breeder income.    The contribution of managerial competence  shown greater than The  socio economic factors. Each other contribution are  33,11 % and  20,70 %.